The journal of physical chemistry letters (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2010)
JPCLett will be an all-Letters-format journal, encompassing all areas covered by JPC A, B, and C, and will replace the current Letters that appear in JPC A, B, and C
Gesehen am 02.01.2013
Keywords: Zeitschrift; Physikalische Chemie